A comparative study of precast column-foundation joints : grouted column shoes versus integrated dry shear keys - Suthep Phosri; Krishna, Chaitanya; Raktipong Sahamitmongkol; Pennung Warnitchai; Punchet Thammarak; Thanakorn Pheeraphan; Royal Thai Government Fellowship (Pathum Thani, Thailand : Asian Institute of Technology, 2025)
The growing adoption of precast concrete columns in modern construction has spurred advancements in connection technologies, particularly through innovative coupling systems and column shoes. Among these, column shoes have emerged as a promising al ternative connection system, offering significant advantages in construction speed, ease of assembly, and maintenance. However, column shoes still require grouting to ensure a proper connection and enhance load transfer between the precast elements. In this study, we proposed a column shoe connection that integrates a dry shear key for connecting columns to foundations, aiming to eliminate the grouting process. We examined its performance, particularly under cyclic loading and shear tests, comparing it to traditional grouted column shoes in precast column-to-foundation connections. In In the first stage, full-scale displacement-controlled cyclic tests were conducted following estab lished loading protocols to evaluate stiffness degradation, strength deterioration, energy dissipation, and equivalent viscous damping. Next, the shear capacity was assessed by applying static loads. In both scenarios, crack propagation was observed and analyzed.The results show that for the cyclic test, the proposed dry shear key connection with the column shoe yielded at a higher load and displacement at 9% drift compared to the grouted connection at 5% drift. Additionally, the failure mechanism of the dry shear key connection shifted the location of the plastic hinge compared to the traditional grouted connection, where the plastic hinge concentrated at the grout. This shift positively af fected the flexural performance. In the shear test, the close male and female socketing of the dry shear key effectively prevented displacement and mitigated concrete spalling when shear load was applied at the base of the column. In contrast, with the traditional grouted column shoe connection, concrete spalling occurred first, leading to the bolts handling the load afterward. Consequently, this resulted in prolonged slip and concentrated stress on the bolt capacity, highlighting the advantages of the dry shear key connection in enhancing load transfer and structural performance.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Engineering in Structural Engineering
Thesis (M. Eng.) - Asian Institute of Technology, 2025
Keywords: Engineering -- Materials -- Testing; Construction Materials -- Testing